THE INFLUENCE OF ORGANIZATIONAL CULTURE ON MANAGERIAL DECISION MAKING: ETHNOGRAPHIC STUDY IN FAMILY FIRM - Ahmad Hanif Ismail; Jumriah Basri (Jurnal Mahasiswa Manajemen, 2024)
This research explores the complexity of the influence of organizational culture on managerial decision-making in family businesses. Utilizing a qualitative ethnographic approach, the study aims to analyze the interaction between traditional values and modern management practices within the context of family businesses in Indonesia. Through in-depth interviews, participatory observations, and document analysis conducted on 5–10 family businesses, the research uncovers the dynamic mechanisms shaping strategic decision-making. The findings reveal that organizational culture plays a critical role in shaping managerial processes, with leadership, traditional values, and adaptive capacity interacting in complex ways. This study provides theoretical contributions to understanding the transformation of family business management and offers a new conceptual model for sustainable decision-making.